Habbits Of Activity School Elementary Students: students' habits at school - Fery Mauliza Fery (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT Physical activity plays a crucial role in the development of children, particularly during their elementary school years. At this stage, students are learning and adapting to new experiences, including those related to their physical health. Developing positive habits related to physical activity can have long-lasting benefits, including better health, improved focus, and enhanced social skills. This article explores the various habits of activity among elementary school students and the factors that influence their participation in physical activities. The habits of activity in elementary school students are shaped by various factors, including school programs, family involvement, and personal interests. Encouraging these habits at a young age can have significant long-term benefits for both physical and mental health. Schools, parents, and communities all play a crucial role in supporting and fostering these habits, helping children develop a strong foundation for a healthy, active life. By integrating physical activity into daily routines, children are not only building strong bodies but also cultivating important skills that will benefit them throughout their lives.